Pengaruh Harga, Brand Image, Dan Brand Ambassador Terhadap Keputusan Pembelian Kahf : (Studi Pada Mahasiswa Prodi Manajemen Angkatan 2020 Universitas Bhayangkara Jakarta Raya) - Muhammad Yusuf Fito Pratama Putra; Dhian Tyas Untari; Heni Rohaeni (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The research carried out aims to determine partially and simultaneously the relationship between price, brand image and brand ambassador on purchasing decisions for the Kahf brand. This research is research with a quantitative approach. The sampling technique used is saturated sampling. The population in this study were all Kahf consumers in the Management study program Class of 2020, Bhayangkara Jakarta Raya University with a sample of 55 respondents. Data processing and hypothesis testing used SPSS 26 software. The research results showed that price partially had a positive and significant effect on purchasing decisions, brand image partially had a positive and significant effect on purchasing decisions, and brand ambassador partially had a positive and significant effect on purchasing decisions. Simultaneous test results show that price, brand image, brand ambassador simultaneously influence purchasing decisions.